Pretreatment of digested manure fibers at high temperature (185°C) with lime added enhances methane production. (September 2022) - Khan, Muhammad Usman; Ahring, Birgitte Kiaer
Abstract: The anaerobic digestion of manure is facing the challenge of limited degradation because of recalcitrant nature of the fibers. In this study different concentrations (1–3%) of lime (CaO) pretreatment for AD of digested manure fibers under thermophilic conditions was evaluated. The results of the study revealed that there was 30.6, 36.4 and 23.5% reduction in cellulose, hemicellulose and lignin fraction of manure fibers during pretreatment when subjected to 3% CaO pretreatment. Degradation of manure fibers also improved because of pretreatment and 40.6% of volatile solids were degraded during AD process. Methane yield was improved by 115.7% in course of this study. Additionally, carbohydrates were main fraction used by anaerobic bacteria to produce methane and 74.9% cellulose and 79.3% hemicellulose was converted to methane in sample which was pretreated using 3% CaO at 185 °C for 30 min. Highlights: Effect of different pretreatments on anaerobic digestion of manure fibers was investigated. Addition of even small concentration of CaO improved the degradation of manure fibers. The methane yield improved 115.7% by thermal pretreatment with 3% CaO added. Degradation of cellulose (82.9%), hemicellulose (86.1%) and VS (40.6%) was highest with 3% CaO added during pretreatment.